Performance analysis of SRM family for unconstrained optimization problems - Syazni Shoid; Universiti Sultan Zainal Abidin . Faculty of Informatics and Computing (2020)
x
1. Introduction -- 2. Literature review -- 3. New Conjugate gradient methods -- 4. Numerical results and discussion -- 5. Conclusion and suggestion
Thesis (Degree of Doctor Philosophy)-Universiti Sultan Zainal Abidin,2020
Includes bibliographical references (leaves 144-154)
Keywords: Universiti Sultan Zainal Abidin -- Faculty of Informatics and Computing -- Dissertations; Calculus of Variations and Optimal Control; Computational Mathematics and Numerical Analysis; Mathematical optimization; Mathematics; Operations Research/Decision Theory; Optimization; Systems Theory, Control